PERAN PENGAWASAN ORANG TUA DALAM PENGGUNAAN SMARTPHONE (STUDI KASUS SDN BENTARSARI 01) - Bambang Sulistiono; Muamar; Dedi Romli Tri Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of parental supervision in shaping students’ smartphone usage patterns among sixth-grade students at SDN Bentarsari 01. The increasing use of smartphones among elementary school children has created both opportunities and challenges, particularly in relation to learning concentration and behavioral development. Uncontrolled smartphone use tends to lead to excessive engagement in entertainment activities, which may negatively affect students’ focus and academic performance. Therefore, parental supervision becomes a crucial factor in directing children toward more responsible and balanced technology use. This research aims to describe the forms of parental supervision and analyze their role in shaping students’ smartphone usage patterns. The study employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving parents and students as research subjects. The selection of informants was conducted purposively based on their relevance to the research focus. The findings reveal two dominant parenting styles: authoritative parenting and indulgent parenting. Authoritative parenting is characterized by balanced control, communication, and guidance, resulting in more structured and responsible smartphone use. In contrast, indulgent parenting tends to provide excessive freedom with minimal supervision, leading to unregulated and entertainment-dominated usage patterns. The study concludes that effective parental supervision plays a significant role not only in controlling smartphone use but also in shaping children’s self-regulation and learning behavior. Thus, a balanced and communicative parenting approach is essential to support productive and educational use of smartphones among students.